IJCM_427A : Profile of HIV Positive Attendees at I.C.T.C. Attavar - A Retrospective Study - Swabu Aishwarya; Saluja Harmeet Singh; Nishad Ankit; Swetha Dhamacharla; Verma Shruti; Dureja Jayati; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: Acquired Immunodeficiency Syndrome (AIDS) continues to pose a significant public health threat worldwide, with India experiencing a substantial burden. Integrated Counseling and Testing Centers (ICTCs) play a pivotal role in addressing HIV/AIDS by providing crucial healthcare access and dispelling misconceptions surrounding the disease. Objectives: To study the profile of PLHIV patients attending ICTC centre. Methodology: This descriptive record-based study was conducted at the ICTC of Kasturba Medical College Hospital, Mangalore, aiming to profile HIV-positive attendees. Data on sociodemographic characteristics, mode of transmission, referrals, and counseling practices were collected from records of 137 seropositive attendees using convenient sampling. Statistical analysis was conducted using SPSS version 11.5. Results: The study revealed that most attendees were male (63.5%), married (78.8%), and aged 40 and above (40.1%). Heterosexual contact was identified as the primary mode of transmission (95.6%), with no cases attributed to blood transfusion. Private health facilities were the primary referrers (72.9%), and ICTC mainly referred patients to Antiretroviral Therapy (ART) centers (72.3%). Post-test counseling included spousal testing (33.6%) and condom counseling (90.5%), with limited condom uptake (18.9%) and follow-up of seropositive attendees (35.8%). Conclusion: The study underscores the critical role of ICTCs in HIV/AIDS management, highlighting trends in attendee profiles, transmission modes, referrals, and counseling practices. It emphasizes the necessity for targeted interventions to enhance follow-up and promote condom usage, alongside continued efforts to mitigate HIV transmission.